Hygromycin B, carboxin and nourseothricin susceptibility of polyunsaturated fatty acid producing Mortierella and Umbelopsis strains - Nyilasi, Ildikó; Kristó, Kata E.; Pálffy, Bettina; Hegyi, Márta; Chandrasekaran, Muthusamy; Kadaikunnan, Shine; Alharbi, Naiyf S.; Papp, Tamás; Vágvölgyi, Csaba (Acta Biologica Szegediensis, 2015)
Mortierella and Umbelopsis species are particularly active in polyunsaturated fatty acid (PUFA) synthesis as they are able to produce many ω-3 and ω-6 PUFAs. Genetic manipulation of the lipid production to generate PUFA overproducing strains and strains with altered PUFA profile requires well-established transformation systems and reliable selectable markers. Therefore, we screened different antifungal agents, which can be used for selection in further transformation experiments. Hygromycin B, carboxin, pyrithiamine and nourseothricin susceptibility of several Mortierella and Umbelopsis isolates was investigated using a broth microdilution method. Pyrithiamine was totally ineffective against all isolates while the other three antifungal agents were active against Mortierella and Umbelopsis strains. Several Mortierella isolates represented high sensitivity to hygromycin B whilst nourseothricin was rather active against Umbelopsis species. Carboxin inhibited the hyphal growth and the spore germination of all isolates completely in low concentrations.